2022
DOI: 10.1038/s41598-021-04150-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, patterns and determinants of dyslipidaemia among South African adults with comorbidities

Abstract: The present study assessed the prevalence, patterns and determinants of dyslipidaemia among South African adults with multi-morbidities. In this study, 614 individuals with DM and hypertension were recruited. Dyslipidaemia was defined as elevated levels of total cholesterol (TC) ≥ 5.2 mmol/L and/or low-density lipoprotein cholesterol (LDL-C) ≥ 2.6 mmol/L, triglycerides (TG) ≥ 1.8 mmol/L and low high-density lipoprotein cholesterol (HDL-C) < 1 mmol/L for men and < 1.2 mmol/L for women. Multivariate regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
3
11
1
Order By: Relevance
“…In Turkish subjects, more females (80.4%) were observed to have lipid abnormalities as compared to males (78.7%) [ 27 ]. In comparison with our study findings, a South African-based study observed a higher frequency of dyslipidemic females (75.79%) as compared to males (24.2%) [ 28 ]. Similar to previous local studies, patients having uncontrolled HbA1c revealed more lipid abnormalities [ 7 ].…”
Section: Discussioncontrasting
confidence: 92%
“…In Turkish subjects, more females (80.4%) were observed to have lipid abnormalities as compared to males (78.7%) [ 27 ]. In comparison with our study findings, a South African-based study observed a higher frequency of dyslipidemic females (75.79%) as compared to males (24.2%) [ 28 ]. Similar to previous local studies, patients having uncontrolled HbA1c revealed more lipid abnormalities [ 7 ].…”
Section: Discussioncontrasting
confidence: 92%
“…Dyslipidaemia was the most commonly occurring disease across all the sites, with the prevalence ranging from 42.7% in men from Navrongo to 87.4% in women from Dikgale. These results are similar to other African studies,36 37 with a recent study by Masilela et al ,38 reporting a prevalence of 76.7% in South African adults receiving care for diabetes and hypertension, and Reiger et al 39 reporting a prevalence of 67.3% in over 4000 adults aged 40 years and older from Agincourt, South Africa. Many of these African studies have reported that low HDL-C is the main driver of the high prevalence of dyslipidaemia, and it is important to debate whether the current international cut-offs for HDL-C, triglyceride and other cholesterol measures are relevant to the African population.…”
Section: Discussionsupporting
confidence: 90%
“…1 A high total cholesterol level in the blood is referred to as hyperlipidaemia, and a normal value is less than 5 mmol/L. 1,2 Different types of cholesterol, including low-density lipoprotein (LDL) cholesterol, triglycerides and high-density lipoprotein cholesterol (HDL-C) form part of the total cholesterol. 1 Dyslipidaemia is a more favourable term than hyperlipidaemia, because it also includes a decreased concentration of HDL-C. 3 Dyslipidaemia, including hypercholesterolaemia can be categorised according to aetiology as either primary/familial or secondary.…”
Section: Introductionmentioning
confidence: 99%